DIVA MOLECULAR DETECTION OF SUSPECTED CASE OF NEWCASTLE AND ENCEPHALOMYLITIS DISEASE IN LAYERS - Amjed. H. Ulaiwi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The aim of the study investigates the molecular diagnosis between (the Avian encephalomyelitis virus and Newcastle disease virus and differentiating the infected from vaccinated animals (DIVA) strategies. The 1st detection by RT-PCR for(PMV-1) as primary detection then, the samples were prepared as in FTA card Whatman® and sent to (AniCon Labs) Germany to detect by one step RT-PCR (DIVA technique) between NDV and AEV genotype. The result of the molecular investigation as primary detection revealed three samples were positive with Ct values (34.0, 26.6, and 35.8) respectively. Then, in the detection of AEV the result showed all samples were negative. finally, by using (DIVA) with two primers to detect general (PMV1-9) by (M-gene) all samples were positive at Ct values (20.8, 20.1, and 25.2) respectively, and then path type by (F gene) to differentiate infected from vaccinated samples also all samples were positive with Ct values (23.8, 23.3 and 23.1) respectively. the study concluded that the samples can differentiate between AEV and NDV by using DIVA strategies to find pathotypes and differentiating between infected and vaccinal isolate based on certain amino acids in the primers.